Emotions and values – a case study of meaning-making in ESE. Issue 4 (21st April 2017) - Manni, Annika; Sporre, Karin; Ottander, Christina
Abstract: With an interest in the role of emotions and values in students' meaning-making in Environmental and Sustainability Education a case study was carried out in a Swedish school-class with students, 12 years of age. During a six-week thematic group-work focusing environmental and sustainability issues related to food, the students were observed and interviewed in their daily school practice. The results are presented here through narrative reporting, and analysed with the use of Dewey's theoretical perspectives on experience, distinguishing three phases in a process: a start, an activity phase and a closure. Martha Nussbaum's theory of emotions is used to assist in the understanding of emotions and values. The study reports on active and independent meaning-making processes in students' group work. The results provide examples of students' meaning-making experiences and the role of emotions and values in them, indicating that more of values are formed and expressed in the concluding phase.